2012
DOI: 10.1016/j.pedneo.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Adrenal Hemorrhage Associated with Scrotal Hematoma: An Unusual Case Report and Literature Review

Abstract: Neonatal adrenal hemorrhage (NAH) is rare and is found in only 0.2% of newborns. Scrotal hematoma (SH) in newborns is also rare. NAH associated with SH is extremely rare, with only 29 cases reported in the literature. Herein, we report a baby boy who presented with SH; after ultrasonography examinations, the diagnosis of NAH associated with SH was made. He received conservative treatment only. From our experience and that of others, appropriate integration of clinical information, physical examination and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
17
1
1
Order By: Relevance
“…To our knowledge, this is the first case of idiopathic scrotal haematoma associated with cryptorchidism. Association of scrotal haematoma with adrenal haemorrhage is reported in the literature [11,12] but it was not present in our case. In the recent literature, only a study by Diamond et al reported five cases of scrotal haematoma mimicking testicular torsion [13]; four of five patients had risk factors for developing a scrotal haematoma.…”
Section: Discussioncontrasting
confidence: 59%
“…To our knowledge, this is the first case of idiopathic scrotal haematoma associated with cryptorchidism. Association of scrotal haematoma with adrenal haemorrhage is reported in the literature [11,12] but it was not present in our case. In the recent literature, only a study by Diamond et al reported five cases of scrotal haematoma mimicking testicular torsion [13]; four of five patients had risk factors for developing a scrotal haematoma.…”
Section: Discussioncontrasting
confidence: 59%
“…He was monitored clinically and radiologically with good outcome. This modality was documented by other workers [8]. Surgical exploration is only indicated if conservative protocol fails or if the hematoma becomes infected.…”
Section: Discussionmentioning
confidence: 95%
“…Few cases of adrenal hemorrhage induced hemoscrotum have been reported in the literature [1, 8, 12]. The condition could be spontaneous or may follow difficult or traumatic delivery [8].…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors include prematurity, prolonged labour, a difficult delivery, macrosomia, perinatal hypoxia, coagulation disorders and septicaemia, though in most cases the aetiology cannot be established [3]. Neonatal adrenal haemorrhage (NAH) can occur in utero, but it usually appears perinatally; 5-10% of the cases involve bilateral haemorrhage; interestingly, in the unilateral cases, right adrenal gland involvement has been reported more frequently [4]. The clinical features are variable: anaemia, persistent indirect hyperbilirubinaemia, abdominal distension with an abdominal mass, and a bluish discolouration of the scrotum [5].…”
Section: Introductionmentioning
confidence: 99%